2013
DOI: 10.1111/cei.12124
|View full text |Cite
|
Sign up to set email alerts
|

The oxidative stress induced in vivo by Shiga toxin-2 contributes to the pathogenicity of haemolytic uraemic syndrome

Abstract: SummaryTypical haemolytic uraemic syndrome (HUS) is caused by Shiga toxin (Stx)-producing Escherichia coli infections and is characterized by thrombotic microangiopathy that leads to haemolytic anaemia, thrombocytopenia and acute renal failure. Renal or neurological sequelae are consequences of irreversible tissue damage during the acute phase. Stx toxicity and the acute inflammatory response raised by the host determine the development of HUS. At present there is no specific therapy to control Stx damage. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 45 publications
(63 reference statements)
1
32
0
Order By: Relevance
“…PMNs were isolated from a pool of heparinized blood obtained from two mice. The cells were harvested by Ficoll-Hypaque separation, followed by dextran sedimentation, as described by Gomez et al (16).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…PMNs were isolated from a pool of heparinized blood obtained from two mice. The cells were harvested by Ficoll-Hypaque separation, followed by dextran sedimentation, as described by Gomez et al (16).…”
Section: Methodsmentioning
confidence: 99%
“…A high peripheral blood PMN count at presentation is the poor-prognosis factor most consistently reported, and the degree of renal impairment has been correlated with the level of activation of circulating PMNs (15). Recently, it has been demonstrated that Stx2 induces an oxidative imbalance in vivo, and ROS production by neutrophils may be one of the major sources of oxidative stress during Stx intoxication (16), contributing to the amplification of microvascular injury in the kidneys (17).…”
mentioning
confidence: 99%
“…Stx2 intoxication induced a marked prothrombotic status and simultaneously a pro-oxidative imbalance demonstrated in both, experimental mouse models [31], and most important in HUS-patients [36,37]. Considering that NAC is a well-known anti-oxidant and glutathione precursor [38], we decided to evaluate if it was able to inhibit Stx2-mediated effects on HGEC cultures.…”
Section: Oxidative Stress Did Not Contribute To Stx2-mediated Damage mentioning
confidence: 99%
“…Furthermore, it is capable to induce oxidative stress and reactive oxidative species (ROS) generation in various cellular types such as endothelial cells [18], platelets [29], and neutrophils [30]. The involvement of the oxidative stress in tissue damage and renal failure processes during Stx-intoxication has also been subject of investigation; oxidative stress is generated by Stx systemically and locally in the kidney and has been shown to enhance platelet activation [31]. Thus, oxidative stress and platelet-derived sCD40L could stimulate each other.…”
Section: Introductionmentioning
confidence: 99%
“…Upon internalization, Stx triggers proinflammatory signals, 55 promotes chemokine release, upregulates leukocyte adhesion molecules and TF, suppresses endothelial TF pathway inhibitor and thrombomodulin, induces platelet-neutrophil interactions, 41 promotes release of TFbearing microparticles, 63 and induces neutrophil production of reactive oxygen species. 64 Stx also interferes with ULVWF cleavage by ADAMTS13 65 and FH, 66 enhancing platelet adhesion/aggregation. Overall, Stx uses multiple means to promote thrombosis, not all of which are sensitive to anticomplement interventions.…”
Section: Shiga Toxin: Direct Effects On Multiple Pathwaysmentioning
confidence: 99%